What we know so far about postural balance training: An exploratory scoping review of nomenclature and related issues. Issue 3 (July 2020) - Imbiriba, Luis Aureliano; Correia, Mariana Rodrigues Alves; Farias, Sara Gonçalves; Silva, Jéssica Meyas; da Nobrega Ferreira, Isabelle; Cavalcanti Garcia, Marco Antonio; Sperandei, Sandro; Macedo, Adriana Ribeiro de
Abstract: Background: Different terms are used to refer to postural balance training, but the ontological debate involving the concepts to pursue nomenclature consensus is unusual. Objective: The goal of this study was to analyze how often the terms balance, neuromuscular, proprioceptive, functional and sensorimotor training/exercise are used in the literature, and to propose a conceptual critical appraisal to determine the most appropriate terminology to address postural balance exercises. Methods: A literature search was conducted in the Scopus electronic database. Eligibility criteria : papers with the selected expressions on the title or keywords, published in English, were included. Results: The most used term was balance training (471 of 1105 included papers). Europe, followed by Asia and North America, had the highest number of publications. In the 21st century, the number of publications increased considerably. However, the terms have conceptual differences and controversies regarding its use. Conclusion: Despite a large variety of exercise types and divergences, balance training seems to be the most suitable term, given it refers to postural equilibrium exercises.